Use of antimicrobials in the intensive care unit of a Loreto public hospital - Marín-Lizárraga, Johan (2024)
Introduction. Inappropriate use of antimicrobials in the Intensive Care Unit (ICU) contributes to bacterial resistance. Objective. The purpose of the present study was to measure the use and type of antimicrobials in patients hospitalized in the Intensive Care Unit of the Loreto Regional Hospital (HRL). Methods. Descriptive study. We reviewed 120 medical records in ICU-HRL patients from January to June 2023. Results. Most patients used antimicrobials (74.2%), indicated for septic shock (42.7%), 1 to 3 antimicrobials (93.2%), with therapy of 1 to 3 days (45%). Of the total number of antimicrobials used, the greatest proportion were bactericides 89 (90.4%), from the cephalosporin family (33.1%) and carbapenemics (23.5%); the most commonly used drugs were ceftriaxone (26.5%) and meropenem (21.1%) by the intravenous route (90.4%). Conclusion. The highest proportion of hospitalized patients use antimicrobials of the cephalosporin and carbapenemics family.